2011
DOI: 10.1111/j.1469-8137.2011.03910.x
|View full text |Cite
|
Sign up to set email alerts
|

OsARF12, a transcription activator on auxin response gene, regulates root elongation and affects iron accumulation in rice (Oryza sativa)

Abstract: Summary• Auxin has an important role in maintaining optimal root system architecture (RSA) that can cope with growth reductions of crops caused by water or nutrient shortages. However, the mechanism of controlling RSA remains largely unclear. Here, we found a limiting factor of RSA -OsARF12 -an auxin response factor whose knockout led to decreased primary root length in rice (Oryza sativa).• OsARF12 as a transcription activator can facilitate the expression of the auxin response element DR5::GFP, and OsARF12 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(143 citation statements)
references
References 53 publications
4
138
1
Order By: Relevance
“…The miR167d targeted and negatively regulated auxin OsARF12 . When OsARF12 was knocked out, the expression of OsMIR , OsIRT1 , and OsSPR1 decreased, resulting in shortened roots, and decreased iron contents in the root tips [67]. In Arabidopsis thaliana , the same phenotype of miR169 was observed, indicating that miR169 plays a role in controlling root architecture [19].…”
Section: Discussionmentioning
confidence: 99%
“…The miR167d targeted and negatively regulated auxin OsARF12 . When OsARF12 was knocked out, the expression of OsMIR , OsIRT1 , and OsSPR1 decreased, resulting in shortened roots, and decreased iron contents in the root tips [67]. In Arabidopsis thaliana , the same phenotype of miR169 was observed, indicating that miR169 plays a role in controlling root architecture [19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we identified a potential AuxRE element in the promoter of OsCKX4. To investigate whether ARFs interact with the OsCKX4 promoter region, we performed yeast one-hybrid assays to test whether OsARF1, OsARF12, and OsARF25, three transcription factors known to act in regulating root development (Waller et al, 2002;Inukai et al, 2005;Qi et al, 2012), bind to the OsCKX4 promoter. Our results showed that only OsARF25 directly binds to the OsCKX4 promoter (Fig.…”
Section: Osckx4 Is Regulated By Auxin and Cytokinin Via Orrs And Osarmentioning
confidence: 99%
“…Furthermore, previous works revealed the mechanisms of IAA-mediated gene expression, signaling and transport in the model dicot Arabidopsis (Leyser 2002;Paponov et al 2005). Cross-talk between auxin and Fe homeostasis suggests that auxin plays a role in the root morphology in response to Fe deficiency and Fe deficiency leads to increased auxin synthesis in Arabidopsis (Schmidt et al 2000;Chen et al 2010) and rice (Qi et al 2012;Shen et al 2015). Oxidative stress or increase in reactive oxygen species (ROS) is a consequence of several abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%